Technical Note: On the size of susceptibility-induced MR image distortions in prostate and cervix in the context of MR-guided radiation therapy - Emmerich, Julian; Pfaffenberger, Asja; Schilling, Rebecca; Denoix, Michael; Maier, Florian; Sterzing, Florian; Bostel, Tilman; Straub, Sina; Laun, Frederik Bernd (Medical Physics, 2018)
PURPOSE: To investigate the extent of MR image distortions in the pelvis caused by susceptibility-induced field inhomogeneities in MR images in the context of a study on MR-guided radiotherapy. METHODS: Using a high-bandwidth double-echo gradient echo sequence, field maps and distortion maps of the pelvis were calculated and evaluated for 219 exams (92 of female and 127 of male patients) to investigate patient-related image distortions caused by susceptibility differences in an ongoing study on MR-guided radiotherapy. The evaluation of distortions in the regions "rectum", "prostate", "cervix", and in a reference region in the gluteus maximus was based on masks drawn by two readers. RESULTS: Distortions in the prostate and cervix were smaller than 0.03 px (0.1 mm) for 99% of voxels, and reached a maximum value of 0.09 px (0.3 mm). In the reference region, maximum distortions were smaller than in the prostate and cervix. CONCLUSIONS: Using a geometric uncertainty of 0.2 px (0.6 mm) in margin definition for organs that are close to the rectum like the prostate and the cervix would be a cautious choice to account for susceptibility-induced distortions that can arise during MR-based treatment guidance for the imaging setting used in this study. Since distortions are inversely proportional to the readout bandwidth of the sequence, safety margins need to be adapted adequately. Additional sources of image distortions like gradient nonlinearities are not included in our margin recommendations and should be considered separately.
EVALuna2:36257